Halitosis - a brief communication (International Seven Journal of Multidisciplinary, 2023)
“Health starts with the mouth”, is a well-known cliché. Teeth and other oral structures, such as the tongue and mucosa, need very careful cleaning to remain free of pathologies. Halitosis or bad breath is a problem that can have different etiologies (e.g., poor oral hygiene and digestive problems). It can have numerous consequences, the main one being social, since living with a person who has bad breath is very unpleasant. Poor hygiene is one of the main factors that cause bad breath. The benefits of excellent oral hygiene include good general health, disease prevention, pleasant breath, and easier social interaction with others. The purpose of this brief communication is to instruct health professionals and patients about oral hygiene, focusing mainly on tongue hygiene that is often neglected among people. DOI:10.56238/isevmjv2n1-009